Three-stage control architecture for cascaded H-Bridge inverters in large-scale PV systems Real time simulation validation - Vavilapalli S.; Umashankar S.; Sanjeevikumar P.; Ramachandaramurthy V.K.; Mihet-Popa L.; Fedk V. (Elsevier Ltd, 2023)
Bridge circuits; Computer architecture; Electric inverters; Insulated gate bipolar transistors (IGBT); Large scale systems; Level control; Maximum power point trackers; Photovoltaic cells; Real time systems; Cascaded H bridge (CHB); Cascaded H-bridge; Cascaded H-bridge inverters; Control architecture; Maximum power point tracking controls; Multilevel; Power conditioning systems; PV inverter; Controllers; air conditioning; building; bypass; computer simulation; dynamic response; irradiation; model validation; photovoltaic system; real time